2018
DOI: 10.1002/pi.5660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen functional groups of reduced graphene oxide on the mechanical and thermal properties of polypropylene nanocomposites

Abstract: Reduced graphene oxide (rGO) with various surface structures was prepared by reducing graphene oxide (GO) with hydrazine hydrate (N 2 H 4 ), sodium borohydride (NaBH 4 ) and L-ascorbic acid, respectively. The resulting rGO were used to fabricate rGO/polypropylene (PP) nanocomposites by a melt-blending method. The surface structure of rGO as well as multifunctional properties of rGO/PP nanocomposites were thoroughly investigated. It was shown that rGO with highest C/O ratio could be obtained by reducing GO with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…This enhancement was mainly brought by the inter-molecular frictions between ARGO nanosheets and PEI matrix. 36,37 However, when more ARGO nanosheets were introduced, the extensive agglomeration of ARGO nanosheets hindered the mutual contacts between ARGO and PEI molecular chains and led to a deteriorated thermal stability. After the incorporation of BT nanoparticles, the T d5 and T d10 of 0.6 wt% BT/ARGO/ PEI further increased to 525.31 C and 548.77 C. The intermolecular friction between heterogeneous three phase enhanced the thermal stability of the composite materials.…”
Section: Resultsmentioning
confidence: 99%
“…This enhancement was mainly brought by the inter-molecular frictions between ARGO nanosheets and PEI matrix. 36,37 However, when more ARGO nanosheets were introduced, the extensive agglomeration of ARGO nanosheets hindered the mutual contacts between ARGO and PEI molecular chains and led to a deteriorated thermal stability. After the incorporation of BT nanoparticles, the T d5 and T d10 of 0.6 wt% BT/ARGO/ PEI further increased to 525.31 C and 548.77 C. The intermolecular friction between heterogeneous three phase enhanced the thermal stability of the composite materials.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was found that the addition of Micro‐P1 increased the content of ‐OH in cement slurry hydration products. The main reason is that GO has a large number of oxygen‐containing functional groups, thus, the characteristic peak strength of ‐OH was enhanced …”
Section: Resultsmentioning
confidence: 99%
“…The main reason is that GO has a large number of oxygen-containing functional groups, thus, the characteristic peak strength of -OH was enhanced. 28,29 3.3.3 | X-ray diffraction analysis X-ray diffraction curves of cement slurry samples were presented in Figure 15. As a result, it was found that the positions of characteristic peaks in X-ray diffraction spectra of cement slurry hydration products are basically the same, mainly including Ca(OH) 2 and C-S-H, as well as some mineral components of unhydrated cement.…”
Section: Infrared Spectrum Analysismentioning
confidence: 99%
“…In our case, graphene does not show functional groups, GO is rich in oxygenated moieties, and RGO shows a certain degree of oxygenated species. Hence, the better interaction of RGO can be related to the decrease of functional moieties as a result of the reduction …”
Section: Resultsmentioning
confidence: 99%